Low-level laser therapy (830 nm) on orthodontic pain: blinded randomized clinical trial - Martins, Isabela Parsekian [UNESP]; Martins, Renato Parsekian [UNESP]; Caldas, Sergei Godeiro Fernandes Rabelo; Dos Santos-Pinto, Ary [UNESP]; Buschang, Peter H.; Pretel, Hermes [UNESP] (Springer Nature, 2018)
The objective of this research was to compare the effect single low-level laser therapy (LLLT) irradiation on pain perception in patients having fixed appliance treatment in the clinic of orthodontics. Sixty-two patients were recruited to participate in this randomized, double-blinded, placebo-controlled study. The patients were assigned to four groups: group I—laser on the right side; group II—placebo on the right side; group III—laser on the left side; group IV—placebo on the left. The laser or placebo was applied before separation, 24 and 48 h after separation of their first permanent molars in the lower arch. Just after the separation, the average of the pain for the placebo group was 1.6, significantly greater than the average of 1.1 registered for the laser group (p = 0.013). After 24 h and before the new irradiation, the values registered among the different groups did not show any differences. In relation to the gender, only after the first irradiation in placebo group, the female had a level of pain (0.1) significantly higher (p = 0.04) compared to male, and after 48 h, the group where the laser was applied had a difference (p = 0.04) among the gender with a value of lower pain for men (0.6) than for women (1.6). The laser irradiation to minimize the pain was only effective when applied immediately after treatment and separation. In general way, there were no differences between the genders, except after the first placebo group irradiation in which the female had a significantly higher level of pain compared to male and after 48 h. The pain cycle observed in this study had its peak in 24 h, both for laser’s and placebo’s group.
Keywords: Facial pain; Laser therapy; LLLT; Orthodontic